Perioperative Care of Patients with Inflammatory Bowel Disease: Focus on Nutritional Support. (23rd September 2018) - Stoner, Patrick L.; Kamel, Amir; Ayoub, Fares; Tan, Sanda; Iqbal, Atif; Glover, Sarah C.; Zimmermann, Ellen M.
Abstract : Patients with inflammatory bowel disease (IBD) commonly require surgery despite the availability of an increasingly large repertoire of powerful immunosuppressive medications for the treatment of IBD. Optimizing patients' care preoperatively is crucial to obtaining good surgical outcomes. This review discusses preoperative assessment and management principles including assessing disease location and activity with cross-sectional or endoscopic imaging, addressing modifiable risk factors (i.e., stopping smoking, weaning steroids, and correcting anemia), and properly managing medications. The major focus of our literature review is the evaluation for malnutrition, a common finding that affects up to 70% of patients with IBD and a well-known, independent risk factor for adverse postoperative outcomes. Our review confirms that whenever feasible, oral or enteral nutrition (EN) is the preferred method of nutritional support; parenteral nutrition (PN) should be reserved for nutritionally deficient IBD patients unable to tolerate EN. In selected patients, recent data demonstrated that the use of preoperative PN resulted in improved nutritional status, fewer postoperative complications, and reduced disease severity. Our review highlights the need for well-designed, prospective trials investigating perioperative nutritional support in patients with IBD. Future studies should perform modern nutritional assessment, standardize for diet, and include patients with UC since this subset of patients is underrepresented in existing studies. In addition, relevant outcome of interest specific to Crohn's disease (CD) patients such as length of small bowel resected, number of anastomoses, and need for an ostomy should be included as these patients may require repeated small bowel resections.